Comparison of Approaches for Notification and Authorization in Pragmatic Clinical Research Evaluating Commonly Used Medical Practices. Issue 11 (November 2017) - Weinfurt, Kevin P.; Bollinger, Juli M.; Brelsford, Kathleen M.; Bresciani, Martina; Lampron, Zachary; Lin, Li; Topazian, Rachel J.; Sugarman, Jeremy
Abstract : Background: For pragmatic clinical research comparing commonly used treatments, questions exist about if and how to notify participants about it and secure their authorization for participation. Objective: To determine how patients react when they seek clinical care and encounter one of several different pragmatic clinical research studies. Research Design: In an online survey using a between-subjects experimental design, respondents read and responded to 1 of 24 hypothetical research scenarios reflecting different types of studies and approaches to notification and authorization (eg, general notification, oral consent, written consent). Subjects: English-speaking US adults 18 years and older. Measures: Willingness to participate in the hypothetical study, acceptability of the notification and authorization approach, understanding of the study, perceptions of benefit/harm, trust, and perception of amount of study information received. Results: Willingness to participate did not differ by notification and authorization approach. Some (21%–36%) of the patients randomized to general notification with an explicit opt-out provision were not aware they would be enrolled by default. Acceptability was greatest for and similar among notification and authorization approaches that actively engaged the patient (eg, oral or written consent) and lower for approaches with less engagement (eg, general notification). Problems of understanding were found among 20%–55% of respondents, depending on the particular scenario. Most respondents (77%–94%) felt that participation in the hypothetical study posed no risks of harm to their health or privacy. Conclusions: Current attitudes about notification and authorization approaches and difficulties understanding pragmatic clinical research pose significant challenges for pragmatic research. Data from this study provide a starting point to developing solutions to these surprisingly complex issues. Abstract : Supplemental Digital Content is available in the text.